Gender and Sexism in Language: A Critical Review of Recent Linguistic Research - Pathak, Akriti (Journal of Advanced Research in English & Education; Vol 9 No 4 (2024): Journal of Advanced Research in English and Education, 2024)
The study of gender and sexism in language has emerged as a significant area of inquiry in linguistics, reflecting broader societal concerns about equity, identity, and representation. This review critically examines recent linguistic research on gender and sexism, exploring key theoretical frameworks, methodologies, and findings. It highlights advancements in understanding gendered language use, the perpetuation of sexism through linguistic structures, and strategies for fostering inclusivity in communication. Moreover, it delves into the cultural and intersectional dimensions of language, analyzing how gender biases are embedded across diverse linguistic and social contexts. The review underscores the role of language in shaping societal norms and power dynamics, emphasizing the transformative potential of inclusive linguistic practices. It also identifies persistent gaps in current research, such as the limited focus on non-Western languages and digital discourse, and suggests directions for future studies to address these challenges and foster more equitable communication frameworks.